[PP.21.19] PREHYPERTENSION AND BEHAVIORAL RISK FACTORS OF CARDIOVASCULAR DISEASE IN RUSSIAN POPULATION: THE RUSSIAN EPIDEMIOLOGY SURVEY ESSE-RF. (September 2017) - Erina, A.; Orlov, A.; Rotar, O.; Konradi, A.; Shalnova, S.; Balanova, Y.; Deev, A.; Zhernakova, Iu.; Baranova, E.; Chazova, I.; Boytsov, S.; Shlyakhto, E.
Abstract : Objective: The study estimates association of PHT with behavioral risk factors of cardiovascular disease in population-based sample of Russian Federation (RF) inhabitants. Design and method: A novel epidemiological survey ESSE-RF random sampling of approximately 1600 participants 25–64 years stratified by age and sex in 12 selected regions (Volgograd, Vologda, Voronezh, Vladivostok, Ivanovo, Kemerovo, Krasnoyarsk, Orenburg, Tomsk, Tyumen, Saint-Petersburg and Northern Osetia-Alania) was performed. All subjects signed informed consent and filled validated questionnaires regarding physical activity, education, nutrition, smoking, concomitant diseases and therapy. Anthropometry, fasting blood tests (lipids, glucose by Abbott Architect 8000 (USA)), blood pressure (BP) measurement were performed. Office BP was registered by OMRON (Japan) twice on right hand in sitting position with calculation of mean BP. Optimal BP was identified as BP less 120/80 mm Hg, PHT as BP = 120–139/80–89 mm Hg, HT as BP more or equal140/90 mm Hg or antihypertensive treatment. Statistical analysis was performed using SPSS Statistics 20. Multivariable logistic regression was performed with adjustment for age and sex. Results: Data analysis was made in 20607 participants 25–65 years (7806 males (37, 9%) and 12801 females (62, 1%)). Figure. No caption available. PHT was significantly associated only with university education OR 0, 78 [95% CI 0, 72;0, 85, p less 0, 001]. University education was significantly associated with lower probability of high salt intake OR 0, 70 [95% CI 0, 66;0, 74], low fruits and vegetable intake OR 0, 75[95% CI 0, 71;0, 80], high fat intake OR 0, 80 [95% CI 0, 74;0, 86], smoking OR 0, 72[95% CI 0, 68;0, 77] and higher probability to have insufficient physical activity OR 2, 69 [95% CI 2, 54;2, 86]. Conclusions: High education might be the important factor for prevention of blood pressure elevation possibly through better behavioral risk factors profile.